STRUKTUR DAN PENGEMBANGAN EMBRIO SOMATIK EKSPLAN DAUN Dyera lowii Hook.f. MELALUI TEKNIK IN-VITRO : Tri Suwarni Wahyudiningsih1*, Issirep Sumardi2 - Admin JHT (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2016)
ABSTRACT The propagation of tree plus Dyera lowii can be anticipated by micropropagation via somatic embryogenesis. The study was aimed: 1). to determine the composition of growth regulators for induction of somatic embryos from leaf explant, 2). To study of the structure and development of somatic embryo D. lowii. The first leaf of seedling was utilized as sources of explants. The base leaf explant growth roots directly on MS (Murashige & Skoog) medium with 2 mg/l Kinetin + 7.5 mg/l IBA, but indirectly via callus phase at IBA 5 mg/l. The middle leaf explant produced somatic embryo resulting yellowish-white and compact texture on MS medium with 0.2 mg/l Benzyl Adenin + 0.5 mg/l IBA. Embryogenic callus cells have formed proembryonic stage: 2-cells, 4-cells, round, globular and heart phase. Keywords: Micropropagation, explant, somatic embryo, pro-embryo, suspensor